Development and Characterization of Thermoresponsive Double‐Network Nanocomposite Hydrogel for Bone Tissue Engineering - Abhishek Indurkar; Kristaps Rubenis; Aldo R. Boccaccini; Janis Locs (Macromolecular Materials and Engineering)
Abstract In this study, a thermoresponsive double‐network (DN) nanocomposite hydrogel is developed. The primary hydrogel network comprises Pluronic P123, while the secondary network comprises gelatinmethacrylate (GELMA) and polyacrylamide (PAM). A systematic approach is adopted to develop DN hydrogels. Initially, the impact of Pluronic P123 concentrationon the mechanical properties of PAM‐GELMA hydrogel is investigated. Results from the tensile strength and the oscillatory shear tests reveal that an increasing P123 concentration has a marginal effect on the storage modulus while significantly reducing the loss modulus of the PAM‐GELMA hydrogel, thereby improving mechanical properties. Notably, DN3 hydrogel containing 7.5w/v% P123 in PAM‐GELMA exhibits osteoid matrix‐like mechanical properties. To further enhance the mechanical properties, citrate‐containing amorphous calcium phosphate (ACP_CIT) is incorporated in DN3 hydrogel at varying concentrations. At a lower concentration of ACP_CIT (0.75 w/v%), the mechanical properties of DN3‐ACP0.75 hydrogel are notably enhanced. Incorporating ACP_CIT in DN3 hydrogel (DN3‐ACP0.75) decreases creep strain, rapid stress relaxation, and reduced water uptake capacity while maintaining the thermoresponsive behavior. Finally, an in vitro analysis confirms the cytocompatibility of the hydrogels with MC3T3‐E1 cells, indicating the potential use in bone tissue engineering.